Effects of biocontrol bacteria and earthworms on the severity of Alternaria brassicae disease and the growth of oilseed rape plants - Ayukea, F. O.; Lagerlöfa, J.; Jorgea, G.; Söderlunda, S.; Muturi, Jamleck; Saroshe, B. R.; Meijere, J. (Elsevier, 2017)
Biological control of plant diseases through the addition of microbial biocontrol agents and the promotion of earthworms can be an environmentally friendly alternative to the chemical control of plant diseases. However, possible risks with biocontrol agents and their interactions with earthworms and other soil biota have not been well studied. The aim of this study was to assess whether the beneficial bacterium Bacillus amyloliquefaciens and the earthworms Aporrectodea caliginosa or Aporrectodea longa could reduce disease in oilseed rape (Brassica napus) challenged with the pathogen Alternaria brassicae. Plant growth and productivity were measured as plant survival, height, biomass, and flower development as well as disease index. A second objective was to assess whether the presence of the bacterium at high concentrations would influence the survival, growth, and reproduction of the earthworms. One outdoor and one greenhouse experiment were performed with Br. napus plants challenged with Al. brassicae inoculated to the plant leaves in the presence or absence of Bacillus amyloliquefaciens inoculated to the root environment and in the presence or absence of earthworms (Ap. caliginosa or Ap. longa) added to the soil. All treatments were replicated three times. In the outdoor experiment, inoculation with Al. brassicae reduced the growth of plants and the addition of Ap. caliginosa increased plant height. In the greenhouse experiment, pairwise comparisons of plants challenged with Al. brassicae showed that treatment with B. amyloliquefaciens led to significantly lower disease index than the treatment with Ap. caliginosa plus B. amyloliquefaciens, while other treatments had intermediate disease indices. The addition of Al. brassicae or B. amyloliquefaciens increased the survival and mass increment of Ap. caliginosa as a main effect when used separately but not when used in combination. This study did not give any clear indication of the usefulness of B. amyloliquefaciens for biocontrol of plant pathogens such as Al. brassicae when growing plants in natural soil. In addition, no significantly positive effects from the tested earthworm species were seen.
Keywords: Plant pathogen repression; Biocontrol agents; Bacillus amyloliquefaciens; Aporrectodea caliginosa; Aporrectodea longa